Precise pretreatment of lignocellulose: relating substrate modification with subsequent hydrolysis and fermentation to products and by-products - Lü, Fan (Biotechnol Biofuels, 2017)
BACKGROUND: Pretreatment is a crucial step for valorization of lignocellulosic biomass into valuable products such as H(2), ethanol, acids, and methane. As pretreatment can change several decisive factors concurrently, it is difficult to predict its effectiveness. Furthermore, the effectiveness of pretreatments is usually assessed by enzymatic digestibility or merely according to the yield of the target fermentation products. The present study proposed the concept of “precise pretreatment,” distinguished the major decisive factors of lignocellulosic materials by precise pretreatment, and evaluated the complete profile of all fermentation products and by-products. In brief, hemicellulose and lignin were selectively removed from dewaxed rice straw, and the cellulose was further modified to alter the crystalline allomorphs. The subsequent fermentation performance of the selectively pretreated lignocellulose was assessed using the cellulolytic, ethanologenic, and hydrogenetic Clostridium thermocellum through a holistic characterization of the liquid, solid, and gaseous products and residues. RESULTS: The transformation of crystalline cellulose forms from I to II and from I (α) to I (β) improved the production of H(2) and ethanol by 65 and 29%, respectively. At the same time, the hydrolysis efficiency was merely improved by 10%, revealing that the crystalline forms not only influenced the accessibility of cellulose but also affected the metabolic preferences and flux of the system. The fermentation efficiency was independent of the specific surface area and degree of polymerization. Furthermore, the pretreatments resulted in 43–45% of the carbon in the liquid hydrolysates unexplainable by forming ethanol and acetate products. A tandem pretreatment with peracetic acid and alkali improved ethanol production by 45.5%, but also increased the production of non-ethanolic low-value by-products by 136%, resulting in a huge burden on wastewater treatment requirements. CONCLUSION: Cellulose allomorphs significantly affected fermentation metabolic pathway, except for hydrolysis efficiency. Furthermore, with the increasing effectiveness of the pretreatment for ethanol production, more non-ethanolic low-value by-products or contaminants were produced, intensifying environmental burden. Therefore, the effectiveness of the pretreatment should not only be determined on the basis of energy auditing and inhibitors generated, but should also be assessed in terms of the environmental benefits of the whole integrated system from a holistic view. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13068-017-0775-3) contains supplementary material, which is available to authorized users.